Ten new species of corticolous pyrenocarpous lichens from NE Brazil - Aptroot, Andre; Andrade, Dannyelly Santos; Mendonça, Cléverton; Lima, Edvaneide Leandro De; Cáceres, Marcela Eugenia Da Silva (Phytotaxa, 2015)
Ten corticolous pyrenocarpous lichens are newly described from different forest biomes in NE Brazil. All were collected in the past two years in Atlantic rain forest or Caatinga vegetation in Pernambuco or Sergipe. The following species are described: Anisomeridium globosum, Pyrenula abditicarpa, P. albonigra, P. aurantiacorubra, P. celaticarpa, P. cinnabarina, P. inspersicollaris, P. musaespora, P. rubrolateralis, and Thelenella lateralis.